What does (or does not) determine persistent corporate high-growth - Stefano Bianchini; Giulio Bottazzi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
Theoretical and empirical studies of industry dynamics have extensively focused on the process of growth. Theory predicts that production efficiency, profitability and financial status are central channels through which some firms can survive, grow and eventually achieve outstanding growth performance. Is the same conceptual framework a convincing explanation to account for persistent corporate high growth? Exploiting panels of Italian, Spanish, and French firms we find no evidence that this is the case: companies experiencing persistent high growth are not more productive nor more profitable, and do not display peculiarly sounder financial conditions than firms that only exhibit high, but not persistent, growth performance. The finding is robust across countries, across sectors displaying different innov ation patterns, and also controlling for demographic characteristics such as age and size.
Keywords: D22; D24; L26; 330; High-growth firms; Persistent high-growth; Productivity; Firm age; Firm size